The Influence of Leadership Style on Teacher Motivation in Islamic Education - St. Maizah; Fina Tamara El-Haris; Irsyad Wira Saputra; Zeinal Abidin (al-Afkar, Journal For Islamic Studies, 2025)
The style or way of leading a principal is something that greatly influences the success of improving teacher performance. Through a good leadership style according to the capacity of the principal, all elements managed will be able to achieve targets according to their main tasks and functions, even the leadership style becomes a picture of the success of efforts to advance educational institutions. One of them is teacher motivation which is a pillar of high work ethic, professionalism, and even increasing self-value as an educator. This article will discuss in more depth the concept and types of leadership styles, so that anyone can choose the leadership style to become a personality in carrying out responsibilities. In the context of Islamic education, the application of a leadership style that is in accordance with Islamic values ​​such as justice, protection, and participation can increase teacher motivation to give their best in the learning process. This study examines various leadership styles that are commonly applied such as transformational, democratic, and authoritarian leadership, and their influence on teacher intrinsic and extrinsic motivation. Therefore, it is important for a leader of an Islamic educational institution to apply a leadership style that encourages teacher professional development, builds harmonious relationships and creates a positive work environment.